ANALISE ISOTÓPICA DE OXIGÊNIO E CARBONO EM MICROFÓSSEIS DA FORMAÇÃO ROMUALDO, CRETACEO INFERIOR, BACIA DO ARARIPE, PERNAMBUCO, NORDESTE DO BRASIL - Araripe, Rilda Cardoso; Oliveira, David Holanda; Tomé, Maria Emília Travassos Rios; Mello, Renata Moura; Barreto, Alcina Magnólia Franca; Sial, Alcides Nóbrega (Geochimica Brasiliensis, 2019)
This work presents the analysis of C and O isotope values behavior in the carapace of ostracodes and foraminifera from the Romualdo Formation, Araripe Basin – PE. The analized samples were collected in three outcrops (Arrojado, Canastra and Cedro) located in the cities of Exu and Araripina. The de δ18O values ranged from -10.1‰ to -10.2‰ VPDB and the δ13C values ranged between -12,6‰ to +2.7‰ VPDB. The results for oxygen data indicate high temperature of waters and the deposition of marine limestones in all outcrops. For the carbon isotopic data in the Arrojado and Canastra outcrops, the values indicate an anoxic environment with high content of organic matter. In Cedro outcrop, a positive variation occurs indicating an increase in primary production, also associated to an anoxic event, and the positive values are interpreted as a transgressive pulse. These results indicate that Cedro outcrop, located in the middlesouth portion of the basin, has environmental characteristics with greater marine influence than in the Arrojado and Canastra outcrops, located in the southwest portion.